2003
DOI: 10.1152/japplphysiol.00892.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nonspecific β-adrenergic stimulation and blockade on blood coagulation in hypertension

Abstract: A hypercoagulable state might contribute to increased atherothrombotic risk in hypertension. The sympathetic nervous system is hyperactive in hypertension, and it regulates hemostatic function. We investigated the effect of nonspecific beta-adrenergic stimulation (isoproterenol) and blockade (propranolol) on clotting diathesis in hypertension. Fifteen hypertensive and 21 normotensive subjects underwent isoproterenol infusion in two sequential, fixed-order doses of 20 and then 40 ng. kg(-1). min(-1) for 15 min/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 30 publications
(33 reference statements)
1
29
1
Order By: Relevance
“…We mention four limitations of our study. First, even though catecholamine infusion consistently elicited coagulation activation in previous studies [25,26], the significant associations between stress hormones and coagulation factors, as related to MBP, do not prove a causal link in our study. Second, to prevent spurious associations by chance, some investigators would require higher levels of significance than we observed in terms of some associations between stress hormones and coagulation measures.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…We mention four limitations of our study. First, even though catecholamine infusion consistently elicited coagulation activation in previous studies [25,26], the significant associations between stress hormones and coagulation factors, as related to MBP, do not prove a causal link in our study. Second, to prevent spurious associations by chance, some investigators would require higher levels of significance than we observed in terms of some associations between stress hormones and coagulation measures.…”
Section: Discussioncontrasting
confidence: 88%
“…Nonetheless, a greater amount of acute norepinephrine release predicted a higher level of acute D-dimer formation. This notion is consistent with early studies showing that catecholamine infusion dosedependently elicited hemostatic changes in plasma within minutes [25,26] consequent to a rapid release of hemostatic molecules from extravascular compartments into the circulation through a b 2 -adrenergic mechanism [15]. Given previous research on greater stress procoagulant reactivity in hypertensives than in normotensives [20,21], the negative association between MBP and the increase of FVIII:C from rest to immediately after stress independent of epinephrine and norepinephrine change was rather unexpected.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Adrenergic infusion and blockade studies in vivo suggest that catecholamines -by stimulating ß2-adrenergic vascular receptors -provoke a rapid release of FVIII, vWF und t-PA stored in the endothelium into the circulation [20,24]. We found that the amount of norepinephrine secretion and the sensitivity of the ß2-adrenergic receptor together explained almost 60% of the variance in thrombin formation with acute mental stress [34].…”
Section: Acute Mental Stressmentioning
confidence: 70%
“…Compared to individuals without atherosclerotic diseases, subjects with atherosclerosis appear to experience an even greater and, therefore, potentially harmful shift in the coagulation-fibrinolysis balance toward hypercoagulability following adrenergic infusions [20,24,25].…”
Section: Adrenergic Activationmentioning
confidence: 99%